Influence of key processing parameters and seeding density effects of microencapsulated chondrocytes fabricated using electrohydrodynamic spraying. (25th June 2018) - Gansau, Jennifer; Kelly, Lara; Buckley, Conor Timothy
Abstract: Cell delivery and leakage during injection remains a challenge for cell-based intervertebral disc regeneration strategies. Cellular microencapsulation may offer a promising approach to overcome these limitations by providing a protective niche during intradiscal injection. Electrohydrodynamic spraying (EHDS) is a versatile one-step approach for microencapsulation of cells using a high voltage electric field. The primary objective of this work was to characterise key processing parameters such as applied voltage (0, 5, 10 or 15 kV), emitter needle gauge (21, 26 or 30 G), alginate concentration (1%, 2% or 3%) and flow rate (50, 100, 250 or 500 μ l min −1 ) to regulate the size and morphology of alginate microcapsules as well as subsequent cell viability when altering these parameters. The effect of initial cell seeding density (5, 10 and 20 × 10 6 cells ml −1 ) on subsequent matrix accumulation of microencapsulated articular chondrocytes was also evaluated. Results showed that increasing alginate concentration and thus viscosity increased overall microcapsule size but also affected the geometry towards ellipsoidal-shaped gels. Altering the electric field strength and needle diameter regulated microcapsule size towards a smaller diameter with increasing voltage and smaller needle diameter. Needle size did not appear to affect cell viability when operating with lower alginate concentrations (1% and 2%), although higher concentrations (3%) and thus higher viscosity hydrogels resulted in diminished viability with decreasing needle diameter. Increasing cell density resulted in decreased cell viability and a concomitant decrease in DNA content, perhaps due to competing nutrient demands as a result of more closely packed cells. However, higher cell densities resulted in increased levels of extracellular matrix accumulated. Overall, this work highlights the potential of EHDS as a controllable and versatile approach to fabricate microcapsules for injectable delivery which can be used in a variety of applications such as drug development or cell therapies.